2008
DOI: 10.1101/sqb.2008.73.012
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Stem Cells of the Prostate and Their Role in Cancer Progression

Abstract: Prostate cancer is a leading cause of cancer-related death in adult men. It can regress dramatically upon antihormonal therapy, but it often recurs in a more aggressive, androgen-independent form. Defining the prostate tissue stem cells (PrSCs) and their involvement in cancer initiation and maintenance may lead to better therapeutics. Using a tissue-regeneration model in which dissociated prostate epithelial cells mixed with inductive mesenchyme give rise to prostatic tubules, we have identified a small popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 94 publications
4
14
0
Order By: Relevance
“…Furthermore, the colony efficiency of the CD44 bright cells was significantly improved following hypoxic pretreatment, whereas the CD44 dim cells did not respond to such hypoxic exposure. Since colony formation and sphere formation capabilities are confined to stem cells [46], [55], [56], these results may support the hypothesis that CD44 bright cells possess stem-like properties in the prostate cancer cells [54].…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, the colony efficiency of the CD44 bright cells was significantly improved following hypoxic pretreatment, whereas the CD44 dim cells did not respond to such hypoxic exposure. Since colony formation and sphere formation capabilities are confined to stem cells [46], [55], [56], these results may support the hypothesis that CD44 bright cells possess stem-like properties in the prostate cancer cells [54].…”
Section: Discussionsupporting
confidence: 67%
“…CD49f (also known as integrin alpha 6, Itga6 ) marks mature prostate basal epithelium (Lukacs et al, 2008; Lukacs et al, 2010; Lawson et al, 2007) and we confirmed it also marks fetal prostate basal epithelium within the urethra and developing prostate buds (Fig. 2C, inset).…”
Section: Resultssupporting
confidence: 77%
“…Epithelial cells quickly lose their self-renewal potential when they are cultured in two-dimensions15. We have developed a three-dimensional culture system to maintain and expand primitive prostate cells that retain the capacity for both self-renewal and differentiation14.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other epithelial stem cell assays, the colony-forming assay is performed in a two-dimensional culture system and measures both proliferative colony-forming activity and differentiation. Colonies are clonal in origin, express basal and luminal keratins, and can be induced to undergo differentiation upon addition of androgen10,14,15. The sphere-forming assay is performed under three-dimensional conditions, as described above.…”
Section: Introductionmentioning
confidence: 99%